1991
DOI: 10.1111/j.1600-0773.1991.tb01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid‐Induced Neural Tube Defects in Mouse and Human: Aspects of Chirality, Alternative Drug Development, Pharmacokinetics and Possible Mechanisms

Abstract: Administration of the antiepileptic drug valproic acid (VPA) during early pregnancy can result in a 1-2% incidence of spina bifida aperta, a closure defect of the posterior neural tube in the human. The predominant defect produced by VPA in the mouse is exencephaly, a closure defect of the anterior neural tube. Recent experiments demonstrate that an appropriate dosing regimen (consecutive doses of VPA on day 9 of gestation) can also result in a low incidence of spina bifida aperta, and a high incidence of spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
196
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 279 publications
(203 citation statements)
references
References 67 publications
3
196
0
3
Order By: Relevance
“…6,7,14 Structure-activity relationship studies conducted in mice strains prone to VPA-associated teratogenicity indicate that to be teratogenic, and to cause neural tube defects in mice embryos, VPA analogues and derivatives should contain a tertiary carbon bound to a carboxylic group, a hydrogen atom, and two alkyl chains. [14][15][16] A VPA derivative lacking any one of these structural requirements has the potential to become a nonteratogenic entity. 6,7,[14][15][16] For example, the corresponding CNS-active amide of VPA valpromide (VPD) that has a carboxamide moiety instead of a carboxylic group is not teratogenic.…”
Section: The Second Generation To Valproic Acid (Vpa)mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7,14 Structure-activity relationship studies conducted in mice strains prone to VPA-associated teratogenicity indicate that to be teratogenic, and to cause neural tube defects in mice embryos, VPA analogues and derivatives should contain a tertiary carbon bound to a carboxylic group, a hydrogen atom, and two alkyl chains. [14][15][16] A VPA derivative lacking any one of these structural requirements has the potential to become a nonteratogenic entity. 6,7,[14][15][16] For example, the corresponding CNS-active amide of VPA valpromide (VPD) that has a carboxamide moiety instead of a carboxylic group is not teratogenic.…”
Section: The Second Generation To Valproic Acid (Vpa)mentioning
confidence: 99%
“…[14][15][16] A VPA derivative lacking any one of these structural requirements has the potential to become a nonteratogenic entity. 6,7,[14][15][16] For example, the corresponding CNS-active amide of VPA valpromide (VPD) that has a carboxamide moiety instead of a carboxylic group is not teratogenic. 17 Similarly, the active metabolite of VPA is 2-ene-VPA, which does not have an ␣-hydrogen to the carboxylic moiety, is also nonteratogenic.…”
Section: The Second Generation To Valproic Acid (Vpa)mentioning
confidence: 99%
“…Some studies suggest that valpromide (similar to VPA, but the carboxyl group is modified to an amide) also has antimanic properties [206]. Valpromide does not inhibit HDAC, does not result in neural tube defects in mouse embryos or the loss of anterior structures that characterizes Xenopus embryos following VPA injection, but does protect against chemically induced seizures in mice [140,[220][221][222][223][224]. Furthermore while the two stereoisomers of VPA have identical antiepileptic properties, only one stereoisomer is teratogenic [224].…”
Section: Valproic Acidmentioning
confidence: 99%
“…1), the primary amide of VPA, is 4 to 10 times more potent than VPA as an AED in rodents and does not appear to induce NTDs in animal models (7). However, the better anticonvulsant potency of VPD, when compared with VPA, and the lack of teratogenicity have little clinical applicability in humans because in humans, VPD acts as a prodrug and is rapidly biotransformed to VPA (8).…”
mentioning
confidence: 99%
“…The evidence to date would suggest that VPA itself, and not one of its known metabolites, is the teratogenic agent (6). Structure-activity relationship studies of VPA derivatives and its analogues have demonstrated that three structural requirements are associated with VPA analogues that induce NTDs: (a) a free carboxyl group; (b) a hydrogen atom in an ␣-position to the carboxyl; and (c) branching on carbon atom two with two alkane chains containing three carbon atoms (7).…”
mentioning
confidence: 99%